2012
DOI: 10.1002/jor.22187
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis develops in the operated joint of an ovine model following ACL reconstruction with immediate anatomic reattachment of the native ACL

Abstract: We tested the hypothesis that immediate reattachment of the native anterior cruciate ligament (ACL) can prevent kinematic changes and the development of osteoarthritis (OA). Five sheep underwent anatomic unilateral ACL reconstruction (ACL-R). Animals from a previous study served as sham (n ¼ 7) or non-operated (n ¼ 17) controls. At 4 points of walking gait, 6 degrees of freedom stifle joint kinematics of ACL-R animals were compared with sham controls at 4 and 20 weeks post-surgery. Gross cartilage, bone, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Neither Calvo et al [93] nor McDevitt et al [96] could find significant differences between the non operated controls and the sham operated knees in their animal models with rabbits and dogs respectively. This was also confirmed later for a large animal model with sheep by O’Brien et al [97]. Therefore the inclusion of a control group of animals without surgical treatment seemed not to be justified when the study protocol was performed also in terms of animal welfare (http://eur-lex.europa.eu, European directives on the protection of animals used for scientific purposes, DIRECTIVE 2010/63/EU, visited July 25th 2016 and [98]).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Neither Calvo et al [93] nor McDevitt et al [96] could find significant differences between the non operated controls and the sham operated knees in their animal models with rabbits and dogs respectively. This was also confirmed later for a large animal model with sheep by O’Brien et al [97]. Therefore the inclusion of a control group of animals without surgical treatment seemed not to be justified when the study protocol was performed also in terms of animal welfare (http://eur-lex.europa.eu, European directives on the protection of animals used for scientific purposes, DIRECTIVE 2010/63/EU, visited July 25th 2016 and [98]).…”
Section: Discussionsupporting
confidence: 70%
“…Thus it seems unlikely, that the sham–operation itself may be the cause of the higher degrees of change in the articular cartilage. Further studies [93,94,95,96,97] were able to show that the cartilage of sham operated animals was not distinguishable from non operated controls in terms of degenerative changes. Neither Calvo et al [93] nor McDevitt et al [96] could find significant differences between the non operated controls and the sham operated knees in their animal models with rabbits and dogs respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The sham control group in this study underwent an identical surgical procedure, but without detachment of ACL, showing osteophyte formations after 20 weeks of recovery similar to the experimental repair group. 14 Future work will need to be done to delineate the degenerative changes associated with the surgical procedure from the graft repair, and whether these changes are alleviated with implementation of postoperative rehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%
“…Following ACL-R surgery, an inflammatory response develops that impacts the integrity of the IPFP tissue and could potentially contribute to the associated degenerative events that compromise the integrity of the knee joint over time [25]. We evaluated the IPFP subsequent to an In previous publications, we reported that early intraarticular inflammation in the synovium of the knee joint correlates to the gross morphological score of the joint following ACL-R surgery [8].…”
Section: Discussionmentioning
confidence: 99%